2018
DOI: 10.2174/1567205015666181002134155
|View full text |Cite
|
Sign up to set email alerts
|

Stroke as a Cause of Death in Death Certificates of Patients with Dementia: A Cohort Study from the Swedish Dementia Registry

Abstract: Introduction: Patients with dementia may be at a higher risk for death from stroke. We aimed to describe characteristics of dementia patients that died from ischemic stroke (IS) in Sweden. Methods: A retrospective longitudinal analysis of prospectively collected data of patients registered into the Swedish Dementia Registry was conducted. Data on causes of death, drugs and comorbidities were acquired from the Swedish nationwide health registers. Deaths were attributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Better cognition may in itself be protective for mortality but ChEIs may also have beneficial systemic effects 27,28 . Stroke and mortality prevention in mild-to-moderate dementia stages are desirable, and stroke prevention could theoretically prolong independent functioning in dementia [41][42][43][44] . Meanwhile, a recent study showed that initiation of antipsychotic treatment was reduced in those treated with ChEIs 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Better cognition may in itself be protective for mortality but ChEIs may also have beneficial systemic effects 27,28 . Stroke and mortality prevention in mild-to-moderate dementia stages are desirable, and stroke prevention could theoretically prolong independent functioning in dementia [41][42][43][44] . Meanwhile, a recent study showed that initiation of antipsychotic treatment was reduced in those treated with ChEIs 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The models were adjusted for age, sex, and CCI (Model 1) and also for type of facility, civil status, reason for admission, planned care, and region (Model 2). These covariates were chosen based on literature as sociodemographic and clinical characteristics associated with mortality in people with dementia [23][24][25][26][27]. The individuals in the hospitalized cohort were followed from the discharge from their first hospitalization for dementia until 31 December 2014 or death, whichever came first.…”
Section: Aim 3: Differences In Survival Between Different Dementia DImentioning
confidence: 99%
“…The individuals in the hospitalized cohort were followed from the discharge from their first hospitalization for dementia until 31 December 2014 or death, whichever came first. We used the date of discharge rather than date of admission to be in line with international registerbased studies on this topic [23][24][25][26][27] and because it is a more reliable information with no missing values.…”
Section: Aim 3: Differences In Survival Between Different Dementia DImentioning
confidence: 99%
“…Ischemic stroke is a major risk factor for vascular dementia and Alzheimer's disease, and it is associated with high neurological disability and mortality. [1][2][3] Within a few minutes, the cascade of reactions caused by ischemic stroke can lead to irreversible functional impairment of nerve tissue in the ischemic core. Ischemic stroke is thought to occur when cerebral artery stenosis and reduction or interruption of regional cerebral blood flow decrease the supply of oxygen and energy to brain tissue, triggering secondary vascular endothelial damage and autonomic nervous dysfunction.…”
Section: Introductionmentioning
confidence: 99%